Investigating the status and skills of Afghan students using the Cognitive Diagnostic Model (CDM) of Afghanistan's 8th grade mathematics. - Mohammad Nasim Wafa (Journal of Medives: Journal of Mathematics Education IKIP Veteran Semarang)
Cognitive diagnostic models (CDMs) are multidimensional multivariate verification flow models with complex structure. In this research, these models were used to investigate the status of eighth grade high school students in mathematics using the TIMMS questionnaire. The cognitive diagnostic test based on 13 attributes including 32 questions was conducted on a sample of 286 students who were selected based on the multi-stage cluster sampling method among the students of Firuzkoh city. IRT and RESMA models were used to determine the psychometric properties of the questions. Data analysis using DINA and DINO models in cognitive diagnostic modeling of mathematics showed that there are 13 attributes that explain the mathematical performance of eighth grade students. The result shows that Afghan students have a weak mastery level in most attributes compared to 45 other countries (the countries that were included in the TIMMS questionnaire) also general results show that the examinees perform better in the field of numbers (0.49), while they perform worse in data and chance (0.12 ). Moreover, there exists some difference in estimating item parameters under the DINA and DINO model, such as Item 3 and Item 27. One possible explanation is that the DINA model is completely compensatory while the DINO model is fully noncompensatory. Similar to the results under DINA model, the SEs of guessing parameters are lower than that of slipping parameters under DINO model